The Implementation of Electronic Money In Increasing Tax Payment Compliance For Taxpayers In Indonesia - Regi Handono (Faculty of Law, Merdeka University Surabaya, 2021)
Tax payment compliance has always been a polemic in any country in the world, including in Indonesia. Indonesia applies a taxation system in the form of self-assessment in which taxpayers have full authority in carrying out their tax obligations. On the one hand, this principle is very good for the tax authorities or the Directorate General of Taxes (DGT), because it reduces their administrative costs. With taxpayers calculating, paying, and reporting their own tax obligations, DGT is on the passive side because it is only a matter of waiting for tax deposits and reports. But on the other hand this also creates new problems. DGT very much depends on the honesty, willingness and level of understanding of taxpayers of their respective tax rules and obligations. The main problem with this principle is the honesty stage. Humans basically will always try with the least possible sacrifice and will try to get the maximum result or benefit. Meanwhile, tax, however its form, is still an expense that must be borne by the taxpayer. This is what causes taxpayers, to always arise reluctance to pay taxes which in the next stage is trying to find ways to reduce tax payments as small as possible. Meanwhile, the state always expects the income from the tax payments of its citizens to ensure the survival and the implementation of development as a whole. For this reason, a breakthrough is needed so that these differences in interests can reach a good common ground for all parties.